Fifteen years of research on oral–facial–digital syndromes: from 1 to 16 causal genes. Issue 6 (13th March 2017) - Bruel, Ange-Line; Franco, Brunella; Duffourd, Yannis; Thevenon, Julien; Jego, Laurence; Lopez, Estelle; Deleuze, Jean-François; Doummar, Diane; Giles, Rachel H; Johnson, Colin A; Huynen, Martijn A; Chevrier, Véronique; et al.
Abstract : Oral–facial–digital syndromes (OFDS) gather rare genetic disorders characterised by facial, oral and digital abnormalities associated with a wide range of additional features (polycystic kidney disease, cerebral malformations and several others) to delineate a growing list of OFDS subtypes. The most frequent, OFD type I, is caused by a heterozygous mutation in the OFD1 gene encoding a centrosomal protein. The wide clinical heterogeneity of OFDS suggests the involvement of other ciliary genes. For 15 years, we have aimed to identify the molecular bases of OFDS. This effort has been greatly helped by the recent development of whole-exome sequencing (WES). Here, we present all our published and unpublished results for WES in 24 cases with OFDS. We identified causal variants in five new genes ( C2CD3, TMEM107, INTU, KIAA0753 and IFT57 ) and related the clinical spectrum of four genes in other ciliopathies ( C5orf42, TMEM138, TMEM231 and WDPCP ) to OFDS. Mutations were also detected in two genes previously implicated in OFDS. Functional studies revealed the involvement of centriole elongation, transition zone and intraflagellar transport defects in OFDS, thus characterising three ciliary protein modules: the complex KIAA0753-FOPNL-OFD1, a regulator of centriole elongation; the Meckel-Gruber syndrome module, a major component of the transition zone; and the CPLANE complex necessary for IFT-A assembly. OFDS now appear to be a distinct subgroup of ciliopathies with wide heterogeneity, which makes the initial classification obsolete. A clinical classification restricted to the three frequent/well-delineated subtypes could be proposed, and for patients who do not fit one of these three main subtypes, a further classification could be based on the genotype.